Mental Illness and Nursing Home Reform: OBRA-87 Ten Years Later - Snowden, Mark; Roy-Byrne, Peter (Psychiatric services (Washington, D.C.), 1998)
OBJECTIVE: This literature review examined data on the effects of nursing home reform initiated by the Omnibus Budget Reconciliation Act of 1987 (OBRA), with particular attention to use of antipsychotic medications, use of physical restraints, and preadmission screening. METHODS: Data on the outcomes of the nursing home reform were obtained from a MEDLINE search of peer-reviewed articles from January 1985 through January 1997 and from PsycINFO from 1967 through 1997. Results and conclusions: Survey and observational data suggest that the reform legislation is having the intended impact, especially in reducing the use of antipsychotic medications and physical restraints in nursing homes. Preadmission screening of nursing home residents with mental illness is the most widely criticized component of the reform, and the component that has been the subject of the fewest data-based studies. More data are needed to describe the economic costs of the reform and to link the reform to improvements in nursing home residents' quality of life.